Hi-purlex facilis: learning hire-purchase law effectively in the new age - Sainan, Zuramaznum; Hilmy Nasrijal, Nasreen Miza (Universiti Teknologi MARA, Kedah, 2023)
Students usually find it taxing to learn a subject which is distinct from the core subjects in their course. Non-law students who are required to pass a law paper often find it difficult to comprehend the legal provisions in the statutes and the cases decided by the courts. While there are books which cater for non-law students, most law books are written in the traditional structure with citation of cases and statutory provisions which are essential sources of the law. However, the traditional structure of reading materials would impede a non-law student’s ability in understanding the lessons as they are not accustomed to the legal writings. As students have different abilities, teaching non-law students require a varied approach to make learning the law less daunting and dreary. Bulky law books can be intimidating and dull, lacking attractive images to sustain a student’s interest. The legal language in law books can be arduous for some students. Inability to understand the lessons delivered would affect students’ performance in the assessments. Students have been found to respond positively to interactive teaching using assorted teaching tools and techniques. Image-based teaching and learning tools increase students’ learning abilities. Brunner’s Scaffolding techniques have been used in legal education for improving the transfer of knowledge. Hi-PurLex Facilis was designed, utilizing the Scaffolding Theory and Retrieval Practice Theory, to facilitate effective learning of law for non-law students. Hi-PurLex Facilis is an imaged-based teaching and learning portal whichprovides a one-stop centre for students to retrieve interactive teaching and learning materials on Hire- Purchase Law. Creative and interesting formative assessment techniques in Hi-PurLex Facilis with reinforce learning activities, enable learners to retain the knowledge learned. Hi-PurLex Facilis is beneficial for students, lecturers and the public as it facilitates the effective transfer of legal knowledge to non-law students and layman.